Effect of slow-release urea inclusion in diets containing modified corn distillers grains on total tract digestibility and ruminal fermentation in feedlot cattle - Ceconi, Irene (2015)
Ruminal degradable intake protein (DIP) deficit may result when cattle are fed diets containing a greater inclusion of processed corn grain and small to moderate inclusion of corn distillers grains (DG). This deficit may arise from greater proportions of rapidly fermentable carbohydrates and RUP in corn grain. Urea-derived N is 100% DIP; however, rates of degradation of carbohydrates and conventional urea (CU) may not match. Therefore, beneficial effects may result from the use of slow-release urea (SRU) sources over CU when added to DIP-deficient diets. An experiment was conducted to evaluate the effect of increasing DIP concentration through inclusion of 1 of 2 SRU sources or CU in DG-containing feedlot diets on ruminal fermentation and total tract digestibility. In addition, an in situ experiment was conducted to characterize N disappearance of urea sources from polyester bags. Four ruminally cannulated steers (initial BW = 588 ± 8 kg) were arranged in a 4 × 4 Latin square design and assigned randomly to 1 of 4 dietary treatments containing 0% (CON) or 0.6% urea in the form of CU (UREA) or SRU as Optigen II (polymer-encapsulated urea; OPTI) or NitroShure (lipid-encapsulated urea; NITRO), and 30% corn earlage, 20% modified corn DG with solubles, 7.8% corn silage, 4.3% dry supplement, and dry-rolled corn (DM basis). Dietary DIP was estimated at 6.6% and 8.3% for CON and urea-containing dietary treatments, respectively. Steers were fed ad libitum once daily. Differences in purine derivatives-to-creatinine (PDC) index between treatments were used as indicators of differences in microbial CP synthesis. Intake of OM, digestibility of OM, NDF, CP, and starch, ruminal pH, total VFA ruminal concentration, and PDC index were not affected by treatment (P ≥ 0.21). Concentration of ammonia-N noticeably peaked at 4 h after feed delivery for cattle fed UREA (treatment × time, P = 0.06) and measured at least 5.5 mg/dL for any treatment and at any hour after feed delivery. During the first 12 h after incubation, N disappearance was greater for CU and NitroShure than Optigen II (urea source × time, P < 0.01). Supplementing DIP through inclusion of CU or SRU did not affect feed intake, digestibility, or most of the ruminal fermentation parameters evaluated, which may relate to the lack of need of urea supplementation in the present experiment. More research is warranted to evaluate the use of SRU in DIP-deficient diets.